Hubungan antara Efikasi Diri dengan Prestasi Belajar Siswa Jurusan Teknik Elektro Industri Studi di SMK YPM 8 Sidoarjo - Ulfah, Maria; Affandi, Ghozali Rusyid (Indonesian Journal Publisher, 2024)
Self-efficacy and learning achievement are very important for every student to have in the learning process. When students have high self-efficacy, students will have power or ease in the learning process. There are difficulties in carrying out learning which include a lack of confidence when presenting in front of the class, easily discouraged when finding difficult assignments and cheating behavior when repeating. The purpose of this study was to determine the relationship between self-efficacy and learning achievement in SMK YPM 8 Sidoarjo. The sample in this study was 129 students majoring in electrical engineering. The data collection technique used the self-efficacy and learning achievement scales using the Likert scale method. The reliability of the self-efficacy scale was tested using the saturated sampling technique and the results obtained from the 19 item reliability yield values were 0.825. The analysis technique used in this study is the Pearson correlation technique assisted by jasp 0.14.1.0 for windows. The results of the analysis of the data obtained with significance (p = 0.072 > 0.05), the hypothesis is accepted, which means that there is a positive relationship between self-efficacy and student achievement in the electrical department of SMK YPM 8 Sidoarjo.